2020
DOI: 10.1183/13993003.00117-2020
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal treatment response to anti-IL-5 monoclonal antibodies in severe eosinophilic asthmatics with airway autoimmune phenomena

Abstract: BackgroundIn clinical trials, the two anti-IL-5 monoclonal antibodies (mAbs, mepolizumab and reslizumab) that are approved to treat severe eosinophilic asthma, reduce exacerbations by approximately 50–60%.ObjectiveTo observe response to anti-IL-5 mAbs in real-life clinical setting, and to evaluate predictors of sub-optimal response.MethodsIn four Canadian academic centres, pre-defined clinical end-points in 250 carefully characterised moderate-to-severe asthmatics were collected prospectively to assess respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 31 publications
6
97
1
4
Order By: Relevance
“…In fact, sputum and blood eosinophils were completely suppressed in all other patients, irrespective of whether they were responders or suboptimal responders. This finding is in direct contrast with those reported for the other anti-IL-5 biologics, where the main cause of treatment failure can be attributed to suboptimal eosinophil suppression-as witnessed in this study-and with data from other mechanistic studies of anti-IL-5 biologic failures [25,52]. While infective exacerbations can occur while being treated with all anti-IL5 biologics, they seem to be more common in a subset of patients with benralizumab for reasons that we do not currently understand.…”
Section: Benralizumab and Airway Infectionscontrasting
confidence: 99%
See 1 more Smart Citation
“…In fact, sputum and blood eosinophils were completely suppressed in all other patients, irrespective of whether they were responders or suboptimal responders. This finding is in direct contrast with those reported for the other anti-IL-5 biologics, where the main cause of treatment failure can be attributed to suboptimal eosinophil suppression-as witnessed in this study-and with data from other mechanistic studies of anti-IL-5 biologic failures [25,52]. While infective exacerbations can occur while being treated with all anti-IL5 biologics, they seem to be more common in a subset of patients with benralizumab for reasons that we do not currently understand.…”
Section: Benralizumab and Airway Infectionscontrasting
confidence: 99%
“…Moreover, a review of 250 patients prescribed anti-IL-5 mAbs (mepolizumab and reslizumab) found that 68.8% had persistent sputum eosinophils (>3%) despite normalization of blood eosinophils. This was associated with elevated sputum anti-EPX IgG, a marker of localized autoimmune response associated with increased eosinophil activity and suboptimal response to biologics [25]. Benralizumab, which is an afucosylated mAb, enhances binding to FcγRIIIa expressed on immune cells such as natural killer (NK) cells and facilitates antibody-dependent cell-mediated cytotoxicity (ADCC).…”
Section: Anti-il-5 Biologics and Asthma Exacerbationsmentioning
confidence: 99%
“…7 Recent observations suggest that galectin-10, coded by the CLC gene, may also regulate airway eosinophilia and this is independent of IL-5. 8 In our cohort study of over 250 severe asthmatic patients treated with mepolizumab or reslizumab, 6 the majority of suboptimal responders (with persistent sputum eosinophils but normal blood eosinophils) had elevated IL-5 in their sputum and not the other potential target proteins, suggesting that sub-optimal response was indeed due to inadequate neutralization of IL-5 in the airway.…”
mentioning
confidence: 82%
“…Underdosing with an anti-IL-5 Mab not only may lead to suboptimal response, but may also potentially worsen both airflow and eosinophilia in 10-15% of patients in whom the treatment is indicated. 6 This tends to happen in patients who already have endogenous immunoglobulin G (IgG)-type antibodies in their sputum to various cell products such as eosinophil peroxidase. Anti-IL-5 forms heterocomplexes with IL-5 and the endogenous IgG autoantibodies, and could potentially activate complement as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation